Temperature management to minimize ground beef aerobic and lactic acid bacteria growth - Mancini, R.A.; Hunt, Melvin C.; Kropf, Donald H.; Hachmeister, K.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Increasing storage and display temperature and time of ground beef significantly increased microbial counts but lean level had no effect. Prolonged storage at abusive temperatures (48°F) caused up to 90% unacceptable chubs and aerobic bacteria counts as high as 7.7 log10 CFU/g, which would render chubs unsatisfactory for further processing, packaging and sale. Thus, ground beef chubs should be stored at 32°F. and as briefly as possible to minimize pre- and post-display microbial counts. Maintaining both optimal storage and display temperatures is critical because combining abusive storage and display conditions resulted in the greatest microbial growth. Shelf life and wholesomeness benefits from maintaining cold (32°F) storage and display temperatures are clearly demonstrated.
Keywords: Beef; Ground beef microbiology; Cold chain management